Pengaruh Blank Holder Force (BHF) Dan Koefisien Gesek Terhadap Cacat Wrinkling Pada Proses Cup Drawing - Agung Trianto, Agung (2016)
Blank holder is the most important part in making drawing experiment and one of vital elements in preventing the wrinkling defect from occurring. During drawing process, the constant role of blank holder is desirable to deal with wrinkling defect. Regarding this, through varying force strength in force in blank holder, the effect of blank holder force on the result of cup drawing process could be revealed. This research started with preparing dies with specified parameter, by adding four holes into blank holder and four bolt taps into dies, to be used as varying blank holder strength later. There were three varying blank holder strengths: 2.352 Nm, 1.7652 Nm and 0.12 Nm in each of its bolts. This research employed cup drawing research method with cylindrical-shaped plate. The product yielded was a cup with upper diameter d1: 46 mm, lowed diameter d2: 30 mm, and depth h: 15 mm. The tested objects (blanks) used was aluminum plate with ultimate load of 1.453 Kgf and thickness of 0.11 mm, zinc plate with ultimate load of 7.280 Kgf with thickness of 0.2 mm, aluminum plate (lead plate) with ultimate load of 8.898 Kgf with thickness of 0.3 mm and aluminum plate (lead plat) with ultimate load of 10.528 Kgf with thickness of 0.32 mm. Diameter of tested objects (blanks) was 64.8 mm. The result of research showed that the best result occurred in plate with ultimate load of 10.528 Kgf, thickness of 0.32 mm and black holder strength of 2.352 Nm. Meanwhile, the plate with ultimate load of 1.453 Kgf and thickness of 0.1 mm encountered torn defect in all of experiments. And the comparison of experiments with and without lubrication found that the effect of friction coefficient on wrinkling defect, the experiment with lubrication had lower wrinkling defect result compared with the one without lubrication.